Policy for Addressing Beggars in the Pilgrimage Tourism Area of Sunan Gunung Jati Tomb - Tiara Ivana; Shafira Amalia Putri; Yanto Heryanto (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research analyzes the tourism policy regarding beggars in the pilgrimage area of the Sunan Gunung Jati Tomb, where begging has become a tradition rooted in Sunan Gunung Jati’s will: "Ingsun entrusts tajug lan fakir kemimian" (I entrust mosques/prayers and the poor). This message is often misinterpreted by the community as justification for the presence of beggars. In tourism policy analysis, it is essential to evaluate how such local traditions intersect with policy objectives, including sustainability, economic impact, and social welfare. Following R. Dye’s public policy framework, effective tourism policy must address community needs while considering stakeholder interests and long-term impacts. This study employs in-depth interviews, field observations, and literature analysis, triangulating data from policy officers and tourists to assess current policy outcomes. Both primary and secondary data are used to ensure comprehensive evaluation. Findings reveal that economic empowerment efforts, such as encouraging the sale of mukena and prayer mats, have not fully resolved the issue. The persistence of beggars highlights the need for a more holistic tourism policy approach, integrating law enforcement, economic development, and community mindset transformation. Sustainable tourism policy should balance economic benefits with social inclusion and cultural preservation, ensuring that interventions are both humane and effective in the long run.